Transseptal puncture using surgical electrocautery in children and adults with and without complex congenital heart disease. Issue 3 (2nd August 2017) - Gowda, Srinath T.; Qureshi, Athar M.; Turner, Daniel; Madan, Nitin; Weigand, Justin; Lorber, Richard; Singh, Harinder R.
Abstract: Background: Atrial transseptal puncture (TSP) for cardiac catheterization procedures remain challenging in children and adults with complex congenital heart disease (CHD). Objectives: We sought to evaluate our experience using radiofrequency (RF) current via surgical electrocautery needle for TSP to facilitate diagnostic and interventional procedures. Methods: Retrospective chart review of all patients (pts) who underwent TSP using RF energy (10–25 W) via surgical electrocautery from three centers from January 2011 to January 2017 were evaluated. Echocardiograms were reviewed to define the atrial septum as normal and complex (thin aneurysmal, thick/fibrotic, synthetic patch material, and extra cardiac conduit). Results: A total of 54 pts underwent 55 successful TSP. Median age was 12.5 years (1 day–54 years) and weight was 52.7 kg (2–162). Indications for TSP included; EP study and ablation procedures in structurally normal hearts ( n  = 24) and in complex atrial septum/CHD and structural heart disease pts ( n  = 30): Electrophysiology study and ablation in 4, diagnostic catheterization in 9, and interventional procedures in 17 pts were performed. Atrial TSP was successful in 54/55 (98%). Atrial perforation with tiny‐small pericardial effusion not requiring intervention was noted in 2 pts. TSP was unsuccessful in one critically ill neonate with unobstructed TAPVR and restricted atrial septum who experienced cardiac arrest requiring CPR, ECMO, and emergent surgery. Conclusions: RF current delivery using surgical electrocautery for TSP is a feasible and an effective option in patients with complex CHD for diagnostic, interventional, and electrophysiology procedures.